Body Composition and Cardiovascular Risk Factors in a Paediatric Population - Sonja Golob Jančič; Mirjam Močnik; Marjetka Švigelj; Nataša Marčun Varda (MDPI AG, 2022)
The aim of our study was to evaluate associations between body composition parameters and several clinical parameters. A total of 206 children and adolescents (120 male, 86 female) were prospectively included. Body impedance measurement was performed in all participants. During the hospital work-up, several clinical parameters such as anthropometric measurements and laboratory and ultrasound findings were obtained and correlated to body composition parameters. There was a significant association between body composition parameters and anthropometric measurements, systolic blood pressure, insulin levels, serum creatinine, urate, liver function tests, triglycerides, cholesterols and apolipoproteins, homocysteine, vitamin D and proteins in 24-h urine. Body composition differed by gender, between participants with and without hepatic steatosis and between patients with and without left ventricular hypertrophy. Interestingly, body composition did not correlate with diastolic blood pressure, pulse wave velocity and intima media thickness. This study showed that several clinical parameters are associated with body composition in children. Obesity and body composition play an important role in the development of other cardiovascular risk factors and are not dependent on fat mass alone, and the latter might be used for cardiovascular risk determination.